Clinical Efficacy of Bibhitaki Vatak in the Management of Pandu Roga with Respect to Iron Deficiency Anemia - Prasad, Nagendra; Badhan, Kavita; Agrawal, Sonam (Recent Updates in Disease and Health Research Vol. 7, 2024)
Iron deficiency anemia (IDA) is prevalent in India due to various factors including dietary deficiencies and chronic blood loss. Pandu, a Pitta predominant Tridoshaja vyadhi mentioned in Ayurveda, shares clinical similarities with IDA. This clinical trial was aimed to assess the efficacy of Bibhitaka Vatak, administered at 500mg twice daily with takra (butter milk) for 30 days followed by a 60-day follow-up period. Twenty patients diagnosed with Pandu (IDA) were included in the study. Symptomatic improvements were observed, including significant reductions in Panduta (pallor), Shrama (breathlessness), Aruchi (anorexia), and Daurbalya (debility). Moderate improvements were noted in Gatrashoola (body ache) and Bhrama (vertigo), while Arohanaayasa (exertional dyspnea) showed suggestive improvement. Highly significant improvements were observed on objective parameters such as Hb%, PCV, MCHC and TIBC after treatment. The findings suggest that Bibhitaka Vatak holds promise as a therapeutic intervention for Pandu, addressing both symptomatic and objective markers associated with IDA.